Sustainable competitiveness in tourism: Strategies and successful practices based on a bibliometric analysis and systematic review - Torres, Liliana Elizabeth Soriano; Ortiz, Karem Bacuy; Zurita, María José Ortiz; Jara, Gabriela Natalia Torres; Paredes, María de Lourdes Larrea (International Journal of Innovative Research and Scientific Studies, 2025)
The impact of sustainable competitiveness on local economies, ecosystems, and cultural resources has made it a vital topic in tourism studies. Sustainable ways to boost the competitiveness of tourist sites have been developed as a result of globalization and the increased need for ethical behavior. The aforementioned tactics underscore the significance of equitable resource management, encompassing economic, environmental, and societal aspects, in order to attract tourists while conserving indigenous resources. Using information from Web of Science and Scopus, this study conducted a comprehensive bibliometric review to identify prominent authors, institutions, and research trends. Database selection, search equation construction, inclusion and exclusion criteria establishment, bibliometric analysis, and software selection were the five steps of the process. Productivity on sustainable competitiveness subjects has increased since 2019, according to the bibliometric analysis, indicating a growing interest in this field. The most influential publications were those published in the Journal of Sustainable Tourism and Sustainability. In order to highlight the importance of interdisciplinary cooperation in tackling sustainability issues in the tourism industry, the study also examined networks of collaboration between institutions, with organizations such as the University of the Philippines emerging as significant participants. Important keywords were "competitiveness," "sustainable tourism," and "sustainable development," suggesting a focus on teamwork to improve sustainability and competitiveness in the industry. The report emphasizes the need for a balance between environmental preservation and economic growth in order to maintain tourism’s competitiveness. In destination management, there is a discernible shift toward collaborative approaches that involve local enterprises, communities, and governments in the adoption of successful sustainable practices. The adoption of sustainability and competitiveness strategies may be impacted by obstacles such as the requirement for sophisticated technology infrastructure and unambiguous data privacy regulations in less developed locations. In order to maximize long-term sustainability, future research should concentrate on integrating cutting-edge technologies and tailoring these tactics to particular geographical circumstances.